2007
DOI: 10.1038/sj.bjc.6603882
|View full text |Cite
|
Sign up to set email alerts
|

An α-fetoprotein-derived peptide reduces the uterine hyperplasia and increases the antitumour effect of tamoxifen

Abstract: Tamoxifen (Tam) is effective for the treatment and prevention of breast cancer. However, it has toxic drawbacks and has limitedduration utility because, over time, human tumours become refractory to Tam. Recently, a new nontoxic peptide, a-fetoproteinderived peptide (AFPep) has been proposed for the treatment and prevention of breast cancer. The purpose of this paper is to determine whether combining AFPep with Tam would increase efficacy and reduce toxicity in experimental models of breast cancer. Low doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We avoided the use of steroid stimulation so as to preclude any trophic effects of steroids on the MCF-7 cells. In other work (36)(37)(38)(39), as well as in this report, we have shown that E 2 stimulates the growth of MCF-7 and T47D cells; it certainly does not inhibit proliferation. As shown clearly in Fig.…”
Section: Discussionmentioning
confidence: 80%
“…We avoided the use of steroid stimulation so as to preclude any trophic effects of steroids on the MCF-7 cells. In other work (36)(37)(38)(39), as well as in this report, we have shown that E 2 stimulates the growth of MCF-7 and T47D cells; it certainly does not inhibit proliferation. As shown clearly in Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Significantly longer mean tumor-free days and lower tumor multiplicity were observed for AFPep-treated groups (64). AFPep prevented breast cancer in a dose-dependent manner and was effective after treatment durations as short as 10 days or as long as 30 days (65). These studies suggest that AFPep can be used as a chemopreventive agent to reduce the incidence of breast cancer in individuals at high risk for development of this disease.…”
Section: Afpep Is Efficaciousmentioning
confidence: 72%
“…This obviously gives pause when considering its use for chemoprevention in otherwise healthy women deemed to be at elevated risk for breast cancer. No side effects have as yet been seen with AFPep, and in experimental animals, AFPep has anti-breast cancer effects equivalent to those of tamoxifen (4). This may be due to the fact that AFPep has a mechanism quite different from that of tamoxifen and other SERMs.…”
Section: Discussionmentioning
confidence: 83%
“…Peptide drugs offer attractive options because the large number of possible combinations of amino acids can lead to exquisite specificity and hence the desired efficacy, and because metabolites of peptides are simple amino acids without toxicity. The purpose of this study was to assess the effects of a novel peptide, shown to be useful for the treatment and prevention of breast cancer in animal models (4)(5)(6), on the estrous cycle and reproductive potential in rats prior to initiation of pre-clinical translational studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation